Projected Motion Sebagai Media Pembelajaran IPA SD Materi Pentingnya Upaya Pelestarian SDA di Lingkungan - Alfina Bakti Pertiwi; Erwin Rahayu Saputra (Universitas Sulawesi Barat, 2022)
The continued existence of conventional learning in elementary school science subjects has left 4th graders without fully understanding the concept of science and of underinterest in student study. Therefore it takes the right media to use the development of technology to give us an understanding of the concept of science. One approach is by using surgical motion media. The purpose of this learning media development is for students to learn in accordance with the cognitive development stage, so that students can understand the science concept, matter of the importance of preserving natural resources (SDA) in the environment in video form. The method of development used in this development is the 4d method, consisting of the defining, design, development, and dissemination stages. Using this learning medium can be a relevant solution for teachers to communicate the science learning material for fourth graders. Keyword: Project Motion, Learning Material, Natural Sciences, Elemantary School